Antihypertensive And Renoprotective Effects Of Hibiscus Sabdariffa Extracts On Doca-Salt Induced And Spontaneously Hypertensive Rats - Ho, Yoke Mei (2022)
Hibiscus sabdariffa is widely used as a folk medicine for hypertension treatment throughout the world. The present study was carried out to develop a standardised, industry friendly and stable oral dosage form incorporating the effective dose of Hibiscus sabdariffa calyces extract, as determined through three animal models, namely spontaneous hypertensive rat model (SHR), DOCA-salt induced hypertensive model and normotensive rat model. Delphinidin 3-sambubioside and cyanidin 3-sambubioside are the major anthocyanins in Hibiscus sabdariffa calyces extract and were known to be very unstable under different storage conditions. The most suitable extraction and concentration methods for Hibiscus sabdariffa calyces water and 50 % ethanolic extracts were maceration and spray dry methods because these methods produced higher total phenolic contents, total flavonoid contents, antioxidant capacity, and anthocyanin contents than reflux boiling and rotary evaporation methods. Both Hibiscus sabdariffa calyces water and 50 % ethanolic extracts were then subjected to pharmacological study and it was found that Hibiscus sabdariffa calyces water extract showed a more potent anti-hypertensive effect. Hibiscus sabdariffa calyces water extract at 500 mg/kg dose was the most effective in reducing blood pressure based on the systolic and diastolic blood pressures in the SHR model and DOCA-salt induced hypertensive model.